Pediatric Respiratory Tract Infections and Circulating Influenza A Virus Subtypes: A Winter Study in Erbil, Iraq - Abdulaziz, Sazan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Influenza and other viral respiratory infections are among the top three leading causes of morbidity and mortality in young children. This study aimed to investigate demographic and clinical characteristics of acute respiratory tract infection (ARTI) and to determine the incidence of influenza A virus subtypes among children in winter in Erbil, Iraq. A cross-sectional study was implemented to investigate the criteria of ARTI in pediatric patients aged ≤5 years who visited Raparin Teaching Hospital for Children from December 1, 2024, to February 28, 2025. A detailed history was collected, and multiplex reverse transcription quantitative polymerase chain reaction was employed for influenza A detection and subtyping. Out of 200 patients, the virus was detected in 14%, with H1N1pdm09 being the predominant subtype (10.5%). Most cases (55%) were hospitalized with severe acute respiratory infection, with ages ≤6 months showing higher susceptibility. Clinically, bronchiolitis was the main clinical diagnosis (66.5%), with hypoxia observed in 36% of cases. Infection among family members was a significant risk factor for pediatric ARTI (p = 0.045). Influenza A showed no significant correlation with hospitalization or age (p = 0.512 and p = 0.987, respectively) but demonstrated strong seasonal variation, peaking in December (p < 0.001). In conclusion, influenza A virus contributed notably, though not predominantly, to pediatric ARTI in Erbil City, with H1N1pdm09 as the predominant subtype and a peak in December. Most cases involved lower respiratory tract disease and hypoxia. Younger age and household infection increase susceptibility, highlighting the need for routine surveillance and preventive measures.